BET Protein Inhibition Regulates Macrophage Chromatin Accessibility and Microbiota-Dependent Colitis - Hoffner O’Connor, Michelle; Berglind, Ana; Kennedy Ng, Meaghan M.; Keith, Benjamin P.; Lynch, Zachary J.; Schaner, Matthew R.; Steinbach, Erin C.; Herzog, Jeremy; Trad, Omar K.; Jeck, William R.; Arthur, Janelle C.; Simon, Jeremy M.; et al. (Frontiers in Immunology, 2022)
Introduction: In colitis, macrophage functionality is altered compared to normal homeostatic conditions. Loss of IL-10 signaling results in an inappropriate chronic inflammatory response to bacterial stimulation. It remains unknown if inhibition of bromodomain and extra-terminal domain (BET) proteins alters usage of DNA regulatory elements responsible for driving inflammatory gene expression. We determined if the BET inhibitor, (+)-JQ1, could suppress inflammatory activation of macrophages in Il10-/- mice. Methods: We performed ATAC-seq and RNA-seq on Il10-/- bone marrow-derived macrophages (BMDMs) cultured in the presence and absence of lipopolysaccharide (LPS) with and without treatment with (+)-JQ1 and evaluated changes in chromatin accessibility and gene expression. Germ-free Il10-/- mice were treated with (+)-JQ1, colonized with fecal slurries and underwent histological and molecular evaluation 14-days post colonization. Results: Treatment with (+)-JQ1 suppressed LPS-induced changes in chromatin at distal regulatory elements associated with inflammatory genes, particularly in regions that contain motifs for AP-1 and IRF transcription factors. This resulted in attenuation of inflammatory gene expression. Treatment with (+)-JQ1 in vivo resulted in a mild reduction in colitis severity as compared with vehicle-treated mice. Conclusion: We identified the mechanism of action associated with a new class of compounds that may mitigate aberrant macrophage responses to bacteria in colitis.